Acurácia da colagem virtual de acessórios ortodônticos em relação ao procedimento direto - Natalice Sousa de Oliveira (2018)
Accuracy of virtual orthodontic attachment bonding in comparison with that of the direct procedure Orthodontic accessory bonding is considered one of the factors that most interferes in the expression of pre-adjusted appliances. Conventional direct or indirect techniques used fail to obtain the ideal position. The combination of novel technologies into indirect bonding digital methods offers new perspectives, seems to improve the accuracy related to the bonding position. The aim of the present study was to compare the accuracy of bonding orthodontic attachments in the digital environment in comparison with the direct procedure, considering the time of clinical experience of the professional. A total of 1120 artificial teeth, constituents of 40 identical models (20 solid sets + 20 digital sets), were equally distributed into two time intervals, between two groups of professionals: Group I: direct bonding (experienced clinicians); Group II: direct bonding (post-graduate students); Group III: virtual bonding (experienced clinicians); Group IV: virtual bonding (post-graduate students). The differences in individual positions between the experimental and reference accessories were measured after three-dimensional superimposition of models in customized software. The analyses were conducted at a level of significance of 5%. The Mann-Whitney test showed significant differences between the mean values of the errors in the vertical dimensions (p = 0.029) and angulation (p = 0.041), between groups I and II, and in the vertical dimension (p =0.020) and angulation (p =0.019), between groups III and IV; the paired Wilcoxon test showed that the differences were significant in the vertical (p < 0.001) and horizontal (p < 0.001) dimensions, between groups I and III and in the vertical (p = 0.006) dimension, between groups II and IV; the Chi-square test showed significant differences in the prevalence of the deviations in all the dimensions (horizontal p < 0.002; vertical p < 0.001; angulation p < 0.001), with time of experience being significant in the horizontal dimension (p = 0.041). Both groups failed to obtain accuracy. The percentage of errors in virtual bonding was significantly lower than those in the linear dimensions (vertical and mesio-distal), and higher in angulation. The percentage of error of the professionals with a longer time of clinical experience was lower in the horizontal dimension. Early diagnosis of deviation in the bonding positions could be of direct benefit to both professional and patient, by foreseeing discrepancies that may lead to undesirable orthodontic movements.